Determinants and market implications of differentiated dividends in Korea. Issue 4 (26th August 2014) - Bae Choi, Bo; Kang, Jangkoo; Lee, Doowon
Abstract : Purpose: – The purpose of this paper is to explore unequal dividend payment policies called differentiated dividends (DDs) in Korea. The characteristics of firms are examined which allocate higher dividends to small shareholders than large shareholders within the same share class. Design/methodology/approach: – Logit analysis is used to compare firms that initiate DDs with those that pay conventional equal dividends. The abnormal market reaction to news of initiation of DDs is also examined. Findings: – Managers of firms facing cash insufficiency are more likely to initiate DDs. The DD scheme is used as a method to cater to high dividend demands in the market. The stock price reaction to the initiation of DDs is positive when the total dividend payments are increased, signifying that the market interprets it as good news. Practical implications: – Firms facing cash insufficiency can avoid an increase in the cost of capital by retaining extra cash from DDs rather than borrowing external funds. Additionally, managers can foster favorable market reactions by using DDs which helps firms in attracting new capital investments. Finally, regulatory bodies can consider encouraging managers to adopt unequal dividend schemes to allow higher dividend payments to small shareholders, especially in countries with weak legal protection for minority shareholders. Originality/value: – Similar unequal dividend policies exist in European countries but there is a lack of research conducted on those policies. The paper provides implications for the strategic use of unequal dividends to maximize firm value.